New data on Siphonaptera from Dinaromys bogdanovi (Rodentia: Muridae) - Brelih, Savo (Scopolia, 2000)
Described is one new species and two new subspecies: Rhadinopsylla dinaromydis sp. n., Ctenophthalmus nifetodes rosickyi ssp. n. and Ctenophtalmus nifetodes milenkovici ssp. n. from Dinaromys bogdanovi. Also described in a female of Ctenophtalmus nifetodes krystufeki. New data are presented, relating to the distribution of some known taxa from this host. Amphipsylla rossica was found on Dinaromys bogdanovi for the first time and we present new data on the host of the subspecies Ctenophthalmus nifetodes tvrtkovici.
Keywords: zoologija; zoology; sesalci; paraziti; bolhe; voluharice